1995
DOI: 10.1046/j.1469-0705.1995.05060384.x
|View full text |Cite
|
Sign up to set email alerts
|

Biometry of the fetal cisterna magna: estimates of the ability to detect trisomy 18

Abstract: Measurements of the fetal cisterna magna were obtained from a prospective sample of patients undergoing diagnostic obstetric ultrasound examinations. These normal measurements were then compared to a retrospective sample of ultrasound scans from fetuses with the diagnosis of trisomy 18 by amniocentesis. The fetal cisterna magna increases in size throughout pregnancy. The sample from fetuses with trisomy 18 was different and had a higher rate of small and large cisterna magnas. After the two samples were mixed,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 0 publications
0
25
0
Order By: Relevance
“…An enlarged cisterna magna is also considered an abnormal cerebellar finding in trisomy 18, implying hypoplasia of the vermis. However, it has been reported that fetal cisterna magna had low sensitivity (26.3%) for identifying trisomy 18 . Therefore, we paid particular attention to the biometry of cerebellar hemispheres in order to detect hypoplasia.…”
Section: Discussionmentioning
confidence: 99%
“…An enlarged cisterna magna is also considered an abnormal cerebellar finding in trisomy 18, implying hypoplasia of the vermis. However, it has been reported that fetal cisterna magna had low sensitivity (26.3%) for identifying trisomy 18 . Therefore, we paid particular attention to the biometry of cerebellar hemispheres in order to detect hypoplasia.…”
Section: Discussionmentioning
confidence: 99%
“…The actual measurement is made on the midline between the posterior surface of the cerebellar vermis and the internal surface of the occipital squama (Snijders and Nicolaides 1994 ;Steiger et al 1995 ). …”
Section: Cisterna Magnamentioning
confidence: 99%
“…Recent technical improvement in ultrasound equipment has allowed more precise measurements of the fetal cisterna magna and transverse cerebellar diameter at 14-40 weeks [1][2][3]. However, the sonographic measurement of the cisterna magna in early pregnancy and in midgestation appears to have a low sensitivity for the detection of fetal trisomy 18 [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…However, the sonographic measurement of the cisterna magna in early pregnancy and in midgestation appears to have a low sensitivity for the detection of fetal trisomy 18 [3][4][5]. In contrast, most reported cases of fetal trisomy 18 associated with an enlarged cisterna magna have been described in the late gestation [3,[6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation